Evaluating Nitrogen Management Options for Reducing Nitrate Leaching from Northeast U.S. Pastures - William L. Stout; James E. Delahoy; Laurence D. Muller; Louis S. Saporito (The Scientific World Journal)
Substantial amounts of nitrate nitrogen NO3-N can leach from intensively grazed pasture in the northeast U.S. where there is about 30 cm of groundwater recharge, annually. Management options for reducing NO3-N leaching were evaluated for this environment using the Cornell Net Carbohydrate and Protein System Model and a recently developed nitrogen leaching index. Management options utilizing energy supplementation of grazing dairy cows could improve nitrogen efficiency within the cow, but would not necessarily reduce NO3-N leaching at the pasture scale if stocking rate was not controlled. The management option of using white clover to supply nitrogen to the pasture decreased NO3-N leaching, but produced less dry matter yield, which in turn reduced stocking rate. The economic returns of reducing NO3-N with these options need to be evaluated in light of milk prices and commodity and fertilizer nitrogen costs. At current prices and costs, the economic benefit from the energy supplementation options is substantial.